Reviewer - Management, Journal of Infrastructure & Facility Asset (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
Paper Writting StipulationPapers on JIFAM - The Journal of Infrastructure & Facility Asset Management Journal is regulated by general stipulation as follows.- Papers must be a real work of the author.- Papers has never been published in other media.- Papers must contain discussion about Infrastructure & Facility Asset Management.- Papers must contains a new discussion, judging based on the discussion that has been published in previous JIFAM.- The paper has to take references from Scientific Journal with minimum of 5 papers.- Paper lengths are limited in 8-16 pages.- Paper Template can be downloaded on the website http://https://iptek.its.ac.id/index.php/jifamScope of TopicJIFAM accepts papers on Infrastructure & Facility Asset Management. The scope of the topic includes, but not limited to,- I & F Function- I & F Demand - Supply- I & F User Behavior- I & F Policy- I & F Planning- I & F Administration Aspects- I & F Operation System- I & F Maintenance System- I & F Evaluation Technique- I & F Disposal- I & F Economical Aspect- I & F Financial Aspect- I & F Management Organization- I & F Spatial Aspects and Environmental AspectsReviewerProf. Dr. Ir. Ria Asih Aryani Soemitro M.Eng, Institut Teknologi Sepuluh Nopember (ITS), SurabayaDr. Trihanyndio Rendy Satria ST., MT., Institut Teknologi Sepuluh Nopember (ITS), SurabayaDr. Mahendra Andiek Maulana ST., MT., Institut Teknologi Sepuluh Nopember (ITS), SurabayaDr. Ir. Ari Widayanti, ST., MT., Universitas Negeri Surabaya (UNESA), Surabaya